2015
DOI: 10.1016/j.canlet.2015.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor and antiandrogen therapy in male breast cancer

Abstract: Cancers arising in the male breast are uncommon. Male breast cancer is a hormone-driven disease that often expresses the estrogen receptor, and antiestrogen therapy represents the mainstay of treatment. Paradoxically, the advent of a wave of antiestrogens eclipsed the therapeutic potential of alternative therapeutic options. At the beginning of the hormonal therapy era the administration of antiandrogens to metastatic male breast cancer patients was proposed. Ever since the use of these compounds has largely b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…AR is expressed across the main molecular subtypes of breast cancer and is gradually becoming recognised as a potential target for therapy in both genders48. Our results confirm these findings and could indicate potential use of anti-androgen therapy to treat MBC as demonstrated successfully in a recent report49.…”
Section: Discussionsupporting
confidence: 86%
“…AR is expressed across the main molecular subtypes of breast cancer and is gradually becoming recognised as a potential target for therapy in both genders48. Our results confirm these findings and could indicate potential use of anti-androgen therapy to treat MBC as demonstrated successfully in a recent report49.…”
Section: Discussionsupporting
confidence: 86%
“…Two alternatively spliced variants encoding distinct isoforms have been described. Androgen hyposensitivity caused by either AR mutations or long CAG repeats might be a causal factor for MBC (Di Lauro et al, 2015). Mutations in the AR gene have been described in MBC and were shown to be associated with complete androgen insensitivity (CAIS) (Wooster et al, 1992;Lobaccaro et al, 1993).…”
Section: Proteinmentioning
confidence: 99%
“…Also, variations of the polyglutamine (CAG) repeat within exon 1 of AR were demonstrated in MBC, with shorter CAG tracts associated with increased AR transcriptional activity, and longer CAG tracts resulting in a suboptimal ligand-mediated stimulation of AR (Young et al, 2000;Song et al, 2012). Immunohistochemistry studies of MBC samples reported AR expression in a range of 34-95% (Di Lauro et al, 2015). In addition to this striking variability, controversy exists, and conflicting data were reported, on the association between AR expression and disease stage and/or survival outcomes.…”
Section: Proteinmentioning
confidence: 99%
“…In FBC on the other hand, ERα clustered with progesterone receptor, whereas AR clustered with ERβ, suggesting an intrinsic difference in hormone receptor biology and hormone receptor dependencies between genders. Specifically in MBC, AR has been shown to be a valid target for treatment in the metastatic setting (Di Lauro et al 2015).…”
Section: Molecular Featuresmentioning
confidence: 99%